Weaning: a prospective investigation into the reality of USL Umbria 1 - Terrinoni, Matteo; Adinolfi, Federica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Weaning represents a critical stage in a child’s development, yet it is frequently surrounded by uncertainty-especially among first-time parents. Such doubts often stem from limited awareness and an abundance of unfiltered information available online. Moreover, informal exchanges among new parents can further complicate matters. To evaluate the real level of parental knowledge on weaning, we conducted a survey at the USL Umbria 1 and the University Hospital of Perugia. Our investigation focused on assessing both the information acquired during antenatal courses and the availability of dedicated resources where parents can seek expert advice on weaning.